Variations in mineral element concentrations of poultry manure biochar obtained at different pyrolysis temperatures, and their effects on crop growth and mineral nutrition - Gunes, A.; Inal, A.; Sahin, O.; Taskin, M. B.; Atakol, O.; Yilmaz, N. (Wiley, 2015)
AbstractThe effect of pyrolysis temperature on the nutritional quality of agricultural biochar is unclear, so better understanding of its properties and how it affects soil nutrient availability and plant growth is needed. Biochars obtained at different pyrolysis temperatures (250, 300, 350 and 400 °C) were characterized by thermogravimetric analyser and Fourier transform infrared spectroscopy. Biochars were applied at a rate of 10 g/kg to find out their effects on the mineral nutrition and growth of lettuce. The experimental results suggested that high biochar temperatures caused oxidation of the mineral elements, breaking of C–C and C–H bonds and removal of aliphatic and peptide groups from the pyrolysed materials. The total concentrations of phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), copper (Cu), manganese (Mn) and boron (B) were increased by increasing pyrolysis temperatures, although water‐soluble concentrations of those elements were greatly reduced (with the exception of K and B). Compared to the control, dry weights of lettuce and maize crops were significantly increased by the biochar treatments obtained at 300 and 350 °C. Biochar treatments significantly increased the P and K concentrations of both plants compared to the control, while concentrations of Ca and Mg in lettuce plants were decreased. Iron, Mn and B concentration of the lettuce plants were reduced and Zn concentration of maize increased by the biochar treatments. It was concluded that in terms of an agricultural product, biochars produced at low temperature are better.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water